PERCEIVED USEFULNESS AND PERCEIVED RISK ON CUSTOMER SATISFACTION IN USING DIGITAL WALLETS - Dinda Maharani Hermawan; Filiya Shaviliya; Siska Ernawati Fatimah (International Journal of Innovative Technologies in Social Science, 2024)
The rapid development of information and communication technology has had a significant impact on human life. One aspect that is affected is the payment system in trading. Cash payment methods are increasingly being shifted by technological advances, to using financial technology in the form of digital wallets. This research aims to test the influence of perceived usefulness and perceived risk on consumer satisfaction. This research uses quantitative methods. The population used in this research is consumers who use Digital Wallets in Cirebon with a total sample taken using the Roscoe formula of 300 respondents. The sampling technique used is probability sampling. The data analysis technique uses Structural Equation Modeling- Partial Least Square (SEM-PLS). The results of this research show that the variable perceived usefulness is more dominant than the variable perceived risk. This is because consumers look at the perceived benefits first compared to the perceived risks.